Precision of the Abbott RealTime Assay in the Detection of Ocular Chlamydia trachomatis in a Trachoma-Endemic Area of Ethiopia - O’Brien, Kieran S. (Am J Trop Med Hyg, 2020)
Nucleic acid amplification tests are increasingly used to detect ocular chlamydia infection in trachoma research and programs. To evaluate the reliability of Chlamydia trachomatis detection by the Abbott RealTime CT/NG assay (Abbott Molecular, Inc., Des Plaines, IL) on the m2000 platform, three conjunctival samples were collected from each of 200 children aged 0–9 years in Ethiopia: two from the right eye and one from the left eye. Four aliquots were processed for each child: two from the first right eye sample, one from the second right eye sample, and one from the left eye sample. Sixty-nine swabs were processed in a U.S. laboratory and 131 in an Ethiopian laboratory. Intra-class correlation coefficients (ICCs) were high when comparing two aliquots from the same swab (ICC ranged from 0.96 to 0.99), two separate swabs from the right eye (0.89–0.91), and one right and one left eye swab (0.87–0.89), indicating reliable chlamydial load assessment across different samples and laboratory settings.